2002
DOI: 10.1038/sj.pcan.4500551
|View full text |Cite
|
Sign up to set email alerts
|

Primary hormonal therapy for prostate cancer: experience with 135 consecutive PSA-ERA patients from a tertiary care military medical center

Abstract: The use of prostate specific antigen (PSA) in the 1990s has brought on a stage migration of prostate cancer. Despite that, many men have still presented with metastatic prostate cancer in the past decade. The use of primary hormone therapy in the PSA era at a tertiary care Army Medical Center is studied in this paper. Charts were reviewed of 135 men who were diagnosed with metastatic prostate cancer and treated with hormone therapy as a primary treatment between 1989 and 1995. Statistical analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…This could be interpreted to mean that young black men were more likely to die than other groups. This current study done exclusively in native black men of sub Saharan Africa found no such relationship though it investigated the broader outcome of PFS; and it corroborates Koff et al findings of no relationships between age, race and PFS [10]. NSAID use was found to be associated with decreased PFS at univariate analysis in this study but this association was lost when PSA nadir was included in multivariate analysis.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This could be interpreted to mean that young black men were more likely to die than other groups. This current study done exclusively in native black men of sub Saharan Africa found no such relationship though it investigated the broader outcome of PFS; and it corroborates Koff et al findings of no relationships between age, race and PFS [10]. NSAID use was found to be associated with decreased PFS at univariate analysis in this study but this association was lost when PSA nadir was included in multivariate analysis.…”
Section: Discussionsupporting
confidence: 84%
“…While pretreatment PSA, PSA velocity and Gleason score have been found to be important predictors of response to therapy and survival in the setting of localized disease [11, 12]; alkaline phosphatase, PSA nadir and time to PSA nadir, PSA half-life have been reported to predict survival following PADT for advanced or metastatic disease [6, 7, 10, 1317]. The importance of these variables has never been investigated in a native African black population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisenberger et al [6], in a review of the National Cancer Institute Intergroup Study ♯0036 for prognostic factors in Stage D2 prostate cancer, noted that the median survival of the 107 African‐American men was 26.4 months, compared with 33.6 months in the 442 CM, and concluded that African‐American race was an adverse prognostic factor in patients with stage D2 prostate cancer treated with hormonal therapy. Similar results were found in other studies [7,8], but other authors did not find race to be an adverse prognostic factor in patients who had their prostate cancer treated with hormonal therapy [9,10]. McLeod et al [9] reported no difference in the outcome of CAB for treating prostate cancer between African‐American men and White men.…”
Section: Discussionsupporting
confidence: 78%
“…We have also shown that ADT does not explain the survival differences observed between AAs and Caucasians. There are conflicting results on the role of androgen in prostate carcinogenesis 14, 37-40, 41-43, 44, 54, 55, 56 and therapeutics. Because CaP is heterogeneous, with hormone-sensitive and hormone-refractory subtypes, hormonal manipulation in CaP is not very clearly understood.…”
Section: Discussionmentioning
confidence: 99%